Research on Eggshell Membrane Separation for High-Purity Calcium Carbonate (CaCO3) Recovery - Phan, Thanh Tam; Nguyen, Thi Thuy; Nguyen, Hai Van (JST: Engineering And Technology For Sustainable Development, 2024)
Along with growing poultry farming, a large amount of eggshell waste is generated daily from food plants and hatcheries. This waste represents a potential biological hazard and is currently being disposed of as environmental pollution. The main composition of eggshells - calcium carbonate - can produce various types of calcium products, such as calcium citrate, calcium lactate, calcium gluconate, … which are beneficial to human health. However, eggshells contain a membrane composed of proteins like collagen and sulfur-rich proteins. These membranes have a fibrous and durable structure, making them difficult to separate from the hard shell layer. The separation of eggshell membranes facilitates the production of high-purity calcium products from calcium carbonate. This study employed three methods to investigate the separation of eggshell membranes: a chemical method using NaOH (1), an enzymatic method utilizing protease enzymes (2), and a combined chemical-enzymatic treatment (3). The results showed that the composition of the eggshells was 94.63% inorganic salts and 3.58% eggshell membranes. The membrane separation efficiency reached 90.63% within 1 hour using method (1). The membrane separation efficiency was relatively high, with Alcalase 2.5L reaching 84.75% and with Protamex reaching 75.62% after 3 hours using the enzymatic method. The combined method achieved a good separation efficiency of 95.04% within 2.25 hours, and the recovered calcium purity reached 99.69%. These results demonstrate the potential for developing an industrial-scale process to treat eggshells and produce high-purity natural calcium products as a valuable source of calcium supplementation for human consumption.